2010
DOI: 10.1109/jsen.2010.2040730
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Calibration Techniques for Smart Temperature Sensors

Abstract: Smart temperature sensors generally need to be trimmed to obtain measurement errors below ±2 • C. The associated temperature calibration procedure is time consuming and therefore costly. This paper presents two, much faster, voltage calibration techniques. Both make use of the fact that a voltage proportional to absolute temperature (PTAT) can be accurately generated on chip. By measuring this voltage, the sensor's actual temperature can be determined, whereupon the sensor can be trimmed to correct for its dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 19 publications
0
25
0
1
Order By: Relevance
“…It can be observed that for more than 50% samples, the accuracy is within 0.2°C in temperature and 0.2 MPa in stress. 3 To further illustrate the accuracy of the proposed selfcalibrated cosensors, we compare the average absolute temperate error (over range [−60°C, 140°C]) for each of the 25 sensors using the one-point calibration technique proposed in [4], as shown in Table I. It is shown that the error for the one-point calibration [4] can be 4.36× as large as that of the proposed self-calibration, and 21 out of the 25 temperature sensors have larger error if calibrated using [4].…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that for more than 50% samples, the accuracy is within 0.2°C in temperature and 0.2 MPa in stress. 3 To further illustrate the accuracy of the proposed selfcalibrated cosensors, we compare the average absolute temperate error (over range [−60°C, 140°C]) for each of the 25 sensors using the one-point calibration technique proposed in [4], as shown in Table I. It is shown that the error for the one-point calibration [4] can be 4.36× as large as that of the proposed self-calibration, and 21 out of the 25 temperature sensors have larger error if calibrated using [4].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Such calibration is usually carried out by putting the chip containing temperature sensors into a thermostated chamber, which can be set to a few known temperature points within sensors' working range. Then, the sensor readings are compared against these actual temperatures for error compensation [3]. However, the time required to stabilize the temperature of the chip under calibration inside the thermostated chamber can be significant, which makes such calibration expensive for massive chip production.…”
Section: Backgroundsmentioning
confidence: 99%
“…Batch calibration can significantly reduce cost, but causes a significant loss of accuracy [1,7]. In addition, although a low-cost voltage calibration technique is proposed to reduce calibration time, the trimming and calibration procedures still need to be implemented manually [9].…”
Section: Introductionmentioning
confidence: 99%
“…1-3 Based on this property since their early discovery, they have been used as temperature change detectors and as thermometers although with low accuracy, even when calibrated. [4][5][6][7][8][9][10] Mainly since the proposition of Verster who showed that using two collector currents: I C1 (V EB1 ) and I C2 (V EB2 ), and their corresponding emitter-base voltages: V EB1 and V EB2 , the transistor temperature could be obtained directly. Although systematically resulting low accurate.…”
mentioning
confidence: 99%
“…6 Other propositions have been made, although, without providing a method to extract the transistor temperature. 10 Here it will be demonstrated that under particular bias conditions the collector current of a bipolar junction transistor indeed provides a probe of the energy distribution of the transistor free charge carrier gases from whose behavior its temperature can be extracted through a rigorous mathematical method. Furthermore, it results that the extracted temperature is independent of every transistor physical parameter constituting a primary thermometer.…”
mentioning
confidence: 99%